Linked Nickel Oxide/Perovskite Interface Passivation for High‐Performance Textured Monolithic Tandem Solar Cells (Adv. Energy Mater. 40/2021). Issue 40 (27th October 2021) - Zhumagali, Shynggys; Isikgor, Furkan H.; Maity, Partha; Yin, Jun; Ugur, Esma; De Bastiani, Michele; Subbiah, Anand S.; Mirabelli, Alessandro James; Azmi, Randi; Harrison, George T.; Troughton, Joel; Aydin, Erkan; et al.
Abstract : Interface Passivation In article number 2101662, Furkan H. Isikgor, Stefaan De Wolf and co‐authors develop a NiO x /perovskite interface passivation strategy using an organometallic dye (N719) molecule. It concurrently passivates both NiO x and perovskite traps and facilitates charge transport across the interface. The self‐assembling nature of N719 allows conformally covering complex surfaces and fabrication of highly efficient textured perovskite/silicon tandem solar cells.